MRI With Gadolinium as a Measure of Blood-Labyrinth Barrier Integrity in Patients With Inner Ear Symptoms: A Scoping Review - Song, Christopher I.; Pogson, Jacob M.; Andresen, Nicholas S.; Ward, Bryan K. (Frontiers in Neurology, 2021)
Objective: Capillaries within the inner ear form a semi-permeable barrier called the blood-labyrinth barrier that is less permeable than capillary barriers elsewhere within the human body. Dysfunction of the blood-labyrinth barrier has been proposed as a mechanism for several audio-vestibular disorders. There has been interest in using magnetic resonance imaging (MRI) with intravenous gadolinium-based contrast agents (GBCA) as a marker for the integrity of the blood labyrinth barrier in research and clinical settings. This scoping review evaluates the evidence for using intravenous gadolinium-enhanced MRI to assess the permeability of the blood-labyrinth barrier in healthy and diseased ears. Methods: A systematic search was conducted of three databases: PubMed, EMBASE, CINAHL PLUS. Studies were included that used GBCA to study the inner ear and permeability of the blood-labyrinth barrier. Data was collected on MRI protocols used and inner ear enhancement patterns of healthy and diseased ears in both human and animal studies. Results: The search yielded 14 studies in animals and 53 studies in humans. In healthy animal and human inner ears, contrast-enhanced MRI demonstrated gradual increase in inner ear signal intensity over time that was limited to the perilymph. Signal intensity peaked at 100 minutes in rodents and 4 hours in humans. Compared to controls, patients with idiopathic sudden sensorineural hearing loss and otosclerosis had increased signal intensity both before and shortly after GBCA injection. In patients with Ménière’s disease and vestibular schwannoma, studies reported increased signal at 4 hours, compared to controls. Quality assessment of included studies determined that all the studies lacked sample size justification and many lacked adequate control groups or blinded assessors of MRI. Conclusions: The included studies provided convincing evidence that gadolinium crosses the blood-labyrinth barrier in healthy ears and more rapidly in some diseased ears. The timing of increased signal differs by disease. There was a lack of evidence that these findings indicate general permeability of the blood-labyrinth barrier. Future studies with consistent and rigorous methods are needed to investigate the relationship between gadolinium uptake and assessments of inner ear function and to better determine whether signal enhancement indicates permeability for molecules other than gadolinium.